The power of symbols. magic, illness and medical act - Cernadas, César Ceriani (Revista del Hospital Italiano de Buenos Aires, 2006)
This work analyzes the relationship between magic and illness from an anthropological viewpoint. In this regard it deals with beliefs and behavior of both physicians and patients in actual medical practice. In doing so, it rests upon anthropological research in the field of health, illness, and care to study those practices labelled as “magical”, which are regarded as primitive and deviant. Through the use of Levi-Strauss’s concept of symbolic efficacy, it enlightens key aspects of the doctor-patient relationship, and also the role played by language, consensus, and trust. Finally, it is intended to build communicative between links disparate medical epistemologies
Keywords: cultural anthropology; magic and illness; symbolic efficacy; doctor-patient relationship